PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN IKAN LAUT DILOSS IKAN BAPAK DEDI (PASAR BARU BALIKPAPAN) - Nikmah Khairunnisa Kamir Kamir; Sukimin Sukimin; Nina Indriastuty (MEDIA RISET EKONOMI [MR.EKO], 2023)
Nikmah Khairunnisa Kamir (2023) The effect of Product Quality, Price and Location on the Decision to Purchase Marine Fish at Mr. Dedi's Fish Loss (Pasar Baru Balikpapan). Advisors: Sukimin and Nina Indriastuty. The purpose of this study was to determine and analyze the effect of product quality, price and location on the purchasing decision of Mr. Dedi's diloss marine fish (Pasar Baru Balikpapan). The data used is a collection of techniques based on interviews and questionnaires. The data analysis method used is an instrument test using validity test, reliability test, classical assumption test, multicollinearity test, heteroscedasticity test, autocorrelation test and using partial test (t). The results of the analysis of the Product Quality variable, Price variable and Location variable have a significant influence on the purchasing decision variables in the purchase of Mr. Dedi's diloss marine fish (Pasar Baru Balikpapan). Keywords: Product quality, price, location and purchasing decisions.